Multicomponent Reactions, Solvent-Free Synthesis of 2-Amino-4-aryl-6-substituted Pyridine-3,5-dicarbonitrile Derivatives, and Corrosion Inhibitors Evaluation - Naglaa F. H. Mahmoud; Ahmed El-Sewedy (Journal of Chemistry)
A number of 2-amino-4-aryl-6-substituted pyridine-3,5-dicarbonitrile derivatives were synthesized via one-pot multicomponent condensation reactions of different aromatic aldehydes with malononitrile and different primary amines, using different molecular ratios and different reaction conditions to achieve considerable product yields. Moreover, we succeed, for the first time to develop a new method to synthesize the aforementioned under the fusion condition without using solvent and catalysts. With this method, a wide range of novel 2-amino-3,5-dicyano-4-aryl-6-substituted aminopyridine derivatives were synthesized with high yields and board substrate of functional groups. The synthesized pyridine derivatives were found to have a corrosion inhibition efficiency, the rate of which increased with the increasing concentration of the derivatives. The structures of the new compounds were elucidated by spectroscopic data and elemental analyses.